William Blake and the impossible history of the 1790s - Makdisi, Saree (University of Chicago Press, 2003)
Modern scholars often find it difficult to account for the profound eccentricities in the work of William Blake, dismissing them as either ahistorical or simply meaningless. But with this pioneering study, Saree Makdisi develops a reliable and comprehensive framework for understanding these peculiarities. According to Makdisi, Blake's poetry and drawings should compel us to reconsider the history of the 1790s. Tracing for the first time the many links among economics, politics, and religion in his work, Makdisi shows how Blake questioned and even subverted the commercial, consumerist, and poli.